Dramaturgi Stand Up Comedian Dalam Menyampaikan Opini dan Kritik Sosial - Yulia Dewi, Gusti Ayu; Aji, Gilang Gusti (The Commercium, 2024)
Stand Up Comedy has become a medium for conveying opinions and social criticism based on restlessness. In achieving the show's goal of being known to a wide audience, comics run the risk of being restricted and restrained. For this reason, the research aims to find out how comic dramaturgy practices in conveying opinions and social criticism. The type of research is qualitative. The research method is phenomenology. The theory used is Erving Goffman's Dramaturgy. The research subjects are comics who have experience of repression and comics who have a critical persona but are still able to carry out their performances amidst the risk of repression. This research found that the type of social criticism regarding political, educational and cultural issues is most vulnerable to repression from outside parties. The forms of comic repression experience range from reprimands to threats and forced removal of social media accounts. There was a fearful response from comics, but there were also comics who continued to run the show. Behind the stage, actors prepare the performance to minimize problems arising from the performance. The aspects that comics pay attention to are (1) Material preparation; (2) Material delivery techniques; (3) Self-positioning; (4) Control the audience by not recording and just posting content.